2012
DOI: 10.1007/s11262-012-0787-9
|View full text |Cite
|
Sign up to set email alerts
|

Delay in virus accumulation and low virus transmission from transgenic rice plants expressing Rice tungro spherical virus RNA

Abstract: Rice tungro, a devastating viral disease of rice in South and Southeast Asia, is caused by the joint infection of a DNA virus, Rice tungro bacilliform virus (RTBV) and an RNA virus Rice tungro spherical virus (RTSV). RTBV and RTSV are transmitted exclusively by the insect vector Green leafhopper (GLH). RTSV is necessary for the transmission of RTBV. To obtain transgenic resistance against RTSV, indica rice plants were transformed using DNA constructs designed to express an untranslatable sense or anti-sense RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 54 publications
0
5
0
1
Order By: Relevance
“…; Verma et al. ; Le et al. ); however, resistance to RTBV is still lacking in available rice germplasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Verma et al. ; Le et al. ); however, resistance to RTBV is still lacking in available rice germplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Although several inbreds have been developed as virus or vector resistant, information on reaction of hybrids to tungro disease is lacking. Recent efforts have been made to develop resistance against RTSV in rice cultivars using breeding and transgenic approaches (Encabo et al 2009;Lee et al 2010;Verma et al 2012;Le et al 2015); however, resistance to RTBV is still lacking in available rice germplasm. The symptoms observation of rice hybrids at different days after inoculation suggests that it is a highly dynamic parameter to phenotype the plants for tungro virus disease.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic grapefruit expressing nontranslatable RNAs of the capsid protein gene of CTV only showed resistance to virus accumulation in two of four plants in one of six lines evaluated (Febres et al, 2008). No transgenic rice plants expressing nontranslatable RNA of the capsid protein coding region of Rice tungro spherical virus (RTSV) showed complete resistance, but some showed a delay in infection with lower virus titers, which prevented transmission by the leafhopper vector (Verma et al, 2012). Several lines of each construct were highly resistant to infection by the corresponding viruses with no detectable virus accumulation (Kung et al, 2009(Kung et al, , 2010.…”
Section: Nontranslatable Sense Rnasmentioning
confidence: 99%
“…Transgenic rice expressing antisense RNA of the RYMV capsid protein gene showed only a delay in virus accumulation (Kouassi et al, 2006). No transgenic rice plants expressing antisense RNA to the replicase gene of RTSV showed complete resistance, but some showed a delay in infection with lower virus titers, which prevented transmission by the leafhopper vector (Verma et al, 2012). Transgenic N. benthamiana expressing antisense RNA to capsid protein gene of PDV showed either resistance or a recovery form of resistance (Raquel et al, 2008).…”
Section: Rna Virusesmentioning
confidence: 99%
“…Rice plants transformed with this construct exhibited lower virus titers, and one of the 2 lines showed very mild symptom (Tyagi et al, 2008). Quite recently, Verma et al found a delayed in virus accumulation and low virus transmission from transgenic rice overexpressing RTSV RNA in either sense or anti-sense direction (Verma et al, 2012). Another study targeting RTSV was by Huet et al, where the authors overexpressed a truncated form of RTSV replicase in rice and found the transgenic rice to be immunized from RTSV infection .…”
Section: Introductionmentioning
confidence: 99%